"Chondroblastoma‐like" epithelioid fibrous histiocytoma: A previously undescribed and potentially confusing variant. (10th December 2017) - Martinez, Anthony P.; Zou, Youran; Billings, Steven D.; Folpe, Andrew L.
Abstract : Background: Epithelioid benign fibrous histiocytoma has been considered a variant of fibrous histiocytoma, but is now considered a distinct entity, typically showing ALK expression. Most show typical morphological features, including an epidermal collarette and large, bland, epithelioid cells. We have recently encountered 2 examples showing an unusual pattern of pericellular calcification, a previously unreported finding. Methods: Available slides were reviewed and clinical follow‐up was obtained. Results: These lesions occurred on the chins of a 16‐year‐old and 19‐year‐old female and showed prominent pericellular calcification in addition to otherwise‐typical features of epithelioid fibrous histiocytoma. By immunohistochemistry, both lesions were intensely positive for ALK protein. Clinical follow‐up (available for 1 case) showed the patient to be disease‐free 5 months after excision. Conclusions: To the best of our knowledge, epithelioid fibrous histiocytomas showing "chondroblastoma‐like" calcification have not been previously reported. The chief significance of this finding seems to be in its potential for confusion with other calcifying tumors of the skin and subcutis. Awareness that epithelioid fibrous histiocytomas may show this unusual morphological finding, careful morphological evaluation and ancillary immunohistochemical studies, including ALK protein, should allow for their confident diagnosis in essentially all instances.